Barriers to and Facilitators for Teachers’ Wellbeing - Gearhart, Cassandra A.; Blaydes, Madison; McCarthy, Christopher J. (Frontiers in Psychology, 2022)
Teaching is widely recognized as a stressful profession, which has been connected to burnout and high turnover of qualified teachers. Despite increasing attention on and promotion of teacher well-being, interventions are often underutilized and demonstrate small effect sizes. It is likely that intervention effectiveness is limited by teachers’ ability to access these well-being resources within the complex educational systems they inhabit. The current study explored teachers’ experiences of barriers to and facilitators for well-being resource access from a socioecological perspective. Teachers’ recommendations for addressing barriers were also explored. Inductive thematic analysis was used to identify themes across four focus groups. Personal barriers (e.g., guilt about self-prioritization), environmental barriers (e.g., mixed-messages about self-care), and improved campus resources (e.g., scheduled opportunities to destress) were common themes. Recommendations for supporting teachers’ well-being activities include campus-wide messaging on time, organizational interventions, and campus-based approaches.